Khanduri Blang in Aceh: Construction of Islamic Law with Qawa’id Fiqhiyyah Approach - Suparmin, Sudirman; Lubis, Asmuliadi (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study aims to analyze the practice of the Khanduri Blang ritual in Samuti Makmur Village, Bireun Regency, Aceh Province from the perspective of Qawa’id Fiqhiyyah. The Khanduri Blang ritual is a religious tradition that involves a series of activities; offerings, and prayers carried out by the Acehnese people in order to commemorate or celebrate an event. This study uses a qualitative approach, data were collected through in-depth interviews, observations, participation and analysis of the Khanduri Blang ritual text. The results of the study show that principles such as mashlahah (benefit), mafsadah (badness), istihsan (virtue), and urf (tradition) in Qawa’id Fiqhiyyah are the basis for assessing the suitability of the ritual with Islamic values. In addition, the Khanduri Blang ritual is not only a series of religious activities, but also a manifestation of how the principles of Qawa’id Fiqhiyyah are rooted in the religious and cultural practices of the Acehnese people. The implications of this study provide a deeper understanding of the relationship between religion, culture and Islamic legal principles in a society.